Radiomics features as predictive and prognostic biomarkers in NSCLC. Issue 3 (4th March 2021) - Bortolotto, Chandra; Lancia, Andrea; Stelitano, Chiara; Montesano, Marianna; Merizzoli, Elisa; Agustoni, Francesco; Stella, Giulia; Preda, Lorenzo; Filippi, Andrea Riccardo
ABSTRACT: Introduction : Radiomics extracts a large amount of quantitative information from medical images using specific data characterization algorithms. This information, called radiomic features, can be combined with clinical data to build prediction models for prognostic evaluation and treatment selection. Areas covered : We outlined a series of studies investigating the correlation between radiomics features and outcome (prognostic) as well as response to therapy (predictive) in non-small cell lung cancer (NSCLC). We performed our analysis both in the setting of early and advanced stage of disease, with a focus on the different therapies and imaging modalities adopted. Expert opinion : The prognostic and predictive potential of the radiomic approach, combined with clinical models, could help decision-making process and guide toward the creation of an optimal and 'tailored' therapeutic strategy for lung cancer patients. However, due to the low reproducibility of most of the conducted studies and the lack of validated results, such a desirable scenario has not yet been translated to routine clinical practice.